2016
DOI: 10.1152/ajpgi.00125.2016
|View full text |Cite
|
Sign up to set email alerts
|

The glial cell-line derived neurotrophic factor: a novel regulator of intestinal barrier function in health and disease

Abstract: Regulation of the intestinal epithelial barrier is a differentiated process, which is profoundly deranged in inflammatory bowel diseases. Recent data provide evidence that the glial cell line-derived neurotrophic factor (GDNF) is critically involved in intestinal epithelial wound healing and barrier maturation and exerts antiapoptotic effects under certain conditions. Furthermore, not only the enteric nervous system, but also enterocytes synthesize GDNF in significant amounts, which points to a potential para-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 66 publications
1
26
0
Order By: Relevance
“…Rat or human EGC have the ability to produce several other n-3 and n-6 polyunsaturated fatty acid derivatives, including the 15-hydroxyeicosatetraenoic acid (15-HETE) and the 11␤-prostaglandin F 2␣ (11␤Ϫ PGF 2 ␣ ), which regulate IEB permeability (72) and healing (24), respectively. The neurotrophic factor glial cell line-derived neurotrophic factor (GDNF) also has IEB-reinforcing properties, especially epithelial antiapoptotic effect, but whether it concerns a direct glio-epithelial effect or it involves neurons or immune cells is not clear (58). In the same way, it is unclear whether these protective effects are due to glial or epithelial GDNF production (57).…”
Section: Egc Regulation Of the Iebmentioning
confidence: 99%
“…Rat or human EGC have the ability to produce several other n-3 and n-6 polyunsaturated fatty acid derivatives, including the 15-hydroxyeicosatetraenoic acid (15-HETE) and the 11␤-prostaglandin F 2␣ (11␤Ϫ PGF 2 ␣ ), which regulate IEB permeability (72) and healing (24), respectively. The neurotrophic factor glial cell line-derived neurotrophic factor (GDNF) also has IEB-reinforcing properties, especially epithelial antiapoptotic effect, but whether it concerns a direct glio-epithelial effect or it involves neurons or immune cells is not clear (58). In the same way, it is unclear whether these protective effects are due to glial or epithelial GDNF production (57).…”
Section: Egc Regulation Of the Iebmentioning
confidence: 99%
“…Recent studies have shown that it also takes part in the regeneration of the intestinal epithelium, maintaining the intestinal epithelial barrier, and reducing intestinal inflammation. In addition, GDNF may have an antiapoptotic effect in the gastrointestinal tract and participate in the signal transmission between enterocytes [57]. As GNDF affects ENS, Starke-Buzetti et al (2008) examined the concentration of GDNF in the ileum and jejunum of rats infected by H. diminuta , and found an increased number of cells producing this neurotrophin.…”
Section: Rat Tapeworm Hymenolepis Diminuta Rudolphi 1819mentioning
confidence: 99%
“…There was observable cytoskeletal reorganization (translocation of F-actin filaments from the cytoplasm to cell membranes) that resulted in more continuous intercellular junctions, without significantly enhancing known adherens and tight junction associated protein expression, or modulating claudin-5 phosphorylation in vitro. 47 A role for GDNF in regulating microvascular endothelial and epithelial tight junction barrier function had also been described in mammalian bloodbrain, blood-retina, blood-testis and intestinal barriers in vitro or in vivo, [49][50][51][52][53][54][55][56] in addition to the in vitro BNB. In order to ascertain whether GDNF regulates mammalian BNB function in vivo, we performed macromolecular permeability assessments of endoneurial microvessels using a validated conditional knockout murine model following non-transecting sciatic nerve crush injury, with appropriate controls.…”
Section: Introductionmentioning
confidence: 98%